3D sensitive volume microdosimeter with improved tissue equivalency: charge collection study and its application in 12C ion therapy. (January 2019) - James, B; Tran, L T; Bolst, D; Prokopovich, D; Reinhard, M; Lerch, M; Petasecca, M; Guatelli, S; Povoli, M; Kok, A; Matsufuji, N; Jackson, M; et al.
Abstract: This research focuses on the characterisation of a new 3D sensitive volume (SV) microdosimeter covered with polyimide – a material which closely mimics human tissue. The electrical and charge collection properties of the device were investigated and its application in 12 C ion therapy were studied. Charge collection studies revealed uniform charge collection and no cross talk between adjacent SVs. To study the microdosimetric response in 12 C ion therapy, the new polyimide mushroom microdosimeter were placed at various positions along the central axis of a 290 MeV/u 12 C ion spread out Bragg peak (SOBP) at the Heavy Ion Medical Accelerator in Chiba (HIMAC), Japan. From these microdosimetric spectra, dose mean lineal energy ( y D ) ¯ and RBE10 results were obtained, with RBE10 increasing from 1.3 at the entrance to 2.7 at the end of the SOBP. The results obtained in this work show that the new generation of mushroom microdosimeters, covered with tissue equivalent polyimide material, are a useful tool for quality assurance in heavy ion therapy applications.